Comparison of the erosion prediction models– A case study of coastal region - NANDGUDE, S. B.; SALUNKHE, S. S.; SHINDE, V. T.; SINGH, M.; SAHU, R. K. (Journal of Soil and Water Conservation, 2021)
Water erosion is one of the most serious problems of soil degradation in the world, the Konkan region of Maharashtra state is particularly exposed to this phenomenon. In recent times, the estimation of soil erosion using empirical models has been a promising research topic as their application over a large and ungauged areas remains a real challenge due to the limited availability and quality of the required data. Using the geospatial technologies, this study aims to estimate and compare the soil erosion rates by the two models of Universal Soil Loss Equation (USLE) and Modiûed Universal Soil Loss Equation (MUSLE) for Ratnagiri district in Konkan region of India. Soil loss of Ratnagiri district by USLE model was found to be43.61 t/ha/yrand sediment yield by MUSLE model was 33.45 t/ha/yr. Sediment yield was more than 70% of total soil loss, which is on higher side by 20% for Konkan region but follows the runoff percentage trend. So, MUSLE model can be used with caution of overestimation in data scare situation in heavy rainfall, hilly region of lateritic soil, wherever runoff gauging stations are not available.